Peran Gembala Sidang dalam Mewujudkan Pendidikan Politik bagi warga Gereja - Arifianto, Yonatan Alex (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2023)
In Christianity which is practiced by believers, its existence cannot be separated from political agendas and practical politics. Because politics is something that aims to build the nation, but sometimes politicians also use various ways beyond reason to seize power. So politics in the church must be separated within the scope of church ministry where the church is a spiritual institution that aims to educate church members to live according to Biblical truths. But politics is also a means for spirituality to educate so that congregation members can understand political paradigms and goals. Using a descriptive qualitative method with a literature study approach, it can be concluded, firstly, the role of the pastor in realizing political education for church members is a priority and important. Second, the pastor of the congregation can facilitate workshops and training in teaching in the political education curriculum, provide political teaching and political enlightenment, and guide his people in Christian life according to the Bible. Third, the Church and the pastoral leadership can also play a role in politics by setting a moral example for their people and defending truth and justice in politics. Because political education aims to increase public awareness of their rights and obligations in the life of the nation and state. Keywords: Pastor; Practical Politics; Political Education, Church citizens. Abstrak: Kekristenan sebagai bagian kehidupan orang percaya memang keberadaannya tidak lepas dari agenda politik dan politik praktis. Sebab politik merupakan sesuatu yang bertujuan membangun bangsa, namun kadang kala para politisi juga melakukan berbagai cara diluar nalar untuk merebut kekuasaan. Maka politik dalam gereja harus dipisahkan dalam ruang lingkup pelayanan gereja dimana gereja adalah lembaga kerohanian yang bertujuan mendidik warga gereja untuk hidup sesuai dengan kebenaran Alkitabiah. Namun politik juga menjadi sarana bagi kerohanian untuk mendidik supaya warga jemaat dapat memahami paradigma dan tujuan politik. Menggunakan metode kualitatif deskritif dengan pendekatan studi pustaka maka dapat disimpulkan, pertama peran gembala sidang dalam mewujudkan pendidikan politik bagi warga gereja sangat menjadi prioritas dan penting. Kedua, gembala sidang dapat memfasilitasi workshop maupun pelatihan dalam pengajaran di kurikulum pendidikan politik, memberikan pengajaran politik dan pencerahan politik, serta membimbing umatnya dalam hidup Kristen sesuai dengan Alkitabiah. Ketiga, Gereja dan kepemimpinan gembala sidang juga dapat berperan dalam politik dengan menjadi teladan moral bagi umatnya dan membela kebenaran dan keadilan dalam politik. Sebab pendidikan politik bertujuan untuk meningkatkan kesadaran masyarakat terhadap hak dan kewajibannya dalam kehidupan berbangsa dan bernegara serta membawa kerohanian yang terus dewasa. Kata kunci:Gembala Sidang; Politik Praktis; Pendidikan Politik, warga Gereja